Ethical moments: future directions for ethical review and ethnography - SIMPSON, BOB (The Journal of the Royal Anthropological Institute, 2011)
The relationship between ethnographic approaches to research and the mechanisms for ethical review that are now being put in place to oversee that research results in significant tensions. This article draws on the author's experience of ethical review systems and interviews with research students in order to explore the nature of these tensions and the consequences they have for how ethnography is conducted now and in the future. A fundamental distinction is identified between an ethics of the body (with a person attached) and an ethics of the person (with a body attached). The former is described in terms of conventional `human subject research' with a genealogy rooted in the Nuremburg Code. The latter opens up the possibility of an ethics of `social subject research' which provokes ethical reflection on what it is to engage with the `open subject'. The article concludes by presenting research as a series of ethical moments which arise throughout research and on into the writing up of ethnography rather than as a single moment at its outset. La relation entre les approches ethnographiques de la recherche et les mécanismes de vérification éthique qui se mettent en place pour superviser ces recherches est une source d'importantes tensions. L'auteur tire ici parti de son expérience des systèmes de revue éthique et d'entretiens avec des étudiants chercheurs pour explorer la nature de ces tensions et leurs conséquences sur la manière dont l'ethnographie est menée aujourd'hui et le sera demain. Il identifie une distinction fondamentale entre l'éthique du corps (auquel une personne est attachée) et l'éthique de la personne (à laquelle un corps est attaché). La première est décrite en termes de « recherche sur un sujet humain » conventionnelle, avec une généalogie remontant au Code de Nuremberg. La deuxième ouvre la possibilité d'une éthique la « recherche sur un sujet social », qui suscite une réflexion éthique sur ce qu'est l'approche du « sujet ouvert ». L'article se conclut en présentant la recherche comme une série de moments éthiques qui surviennent à chaque étape du travail, jusqu'à la mise par écrit de l'ethnographie, plutôt que comme un moment unique au tout début.